The Effect of 17% Ethylenediaminetetraacetic Acid and 10% Citric Acid Solutions with Manual and Ultrasonic Agitation on Smear Layer Removal and Intraradicular Dentine Erosion: A Scanning Electron Microscope Evaluation - Alessandro Rodrigo Maggioni; Helena Rosa Campos Rabang; Brenda Paula Figueiredo de Almeida Gomes; Luiza Gonçalves Roma; Isabel Coelho Gomes Camões (Portal de Periódicos da Marinha do Brasil, 2020)
This study evaluated the ex vivo effectiveness of different final irrigation protocols in smear layer removal and intraradicular dentine erosion. Thirty five extracted human canines were instrumented and randomly divided, according to final rinse techniques used, into 7 groups: 1 (ED3M) and 3 (ED3US), 17% EDTA for 3 minutes with manual and ultrasonic agitation, respectively; 2 (CA30M) and 4 (CA30US), 10% citric acid for 30 seconds with manual and ultrasonic agitation, respectively; 5 (CA3M) and 6 (CA3US), 10% citric acid for 3 minutes with manual and ultrasonic agitation, respectively; and, 7 (Na3), 5.25% NaOCl for 3 minutes without agitation (control). All specimens then were irrigated with 5.25% NaOCl, split lengthwise, and examined under scanning electron microscopy (SEM) in apical, middle and coronal thirds. Data were analyzed with Kruskal-Wallis and Mann-Whitney tests. The effectiveness of 17% EDTA and 10% citric acid in removing smear layer was significantly greater than 5.25% NaOCl (control). There were no significant differences among final irrigation protocols in smear layer removal or erosive effects. However, when comparing the thirds in groups 1 (ED3M) and 2 (CA30M), the least smear layer removal and erosion was seen in the apical third, but the group 4 procedure (CA30US) was more effective than 1 (ED3M) (p=0.0004), 2 (CA30M) (p=0.0018) or 3 (ED3US) (p=0.0003) in smear layer removal for the apical third. It was concluded that protocols used in this study were similar in smear layer removal and erosive effects.